2021
DOI: 10.3831/kpi.2021.24.2.41
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Complementary Medicine on Pain Relief and Wound Healing after Cesarean Section: A Systematic Review

Abstract: Objectives Cesarean sections are one of the common surgical procedures around the world. Management of cesarean section side effects, including pain, hematoma, delayed wound healing, is of particular importance in maintaining maternal health and ability to care for the baby. The tendency to use complementary medicine strategies is on the rise because of the easy treatment with low side effects. The purpose of this study was to systematically review the efficacy and safety of clinical trials perfor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 32 publications
0
5
0
4
Order By: Relevance
“…'nın yaptığı sistematik derlemede de bazı bitkiler ile yapılan aromaterapilerin sezaryen sonrası ağrıyı azaltmada etkili olduğu bildirilmiştir. 18 Lakhan ve ark. da postoperatif ağrının tedavisinde aromaterapinin etkili olduğunu bildirmişlerdir.…”
Section: Discussionunclassified
See 3 more Smart Citations
“…'nın yaptığı sistematik derlemede de bazı bitkiler ile yapılan aromaterapilerin sezaryen sonrası ağrıyı azaltmada etkili olduğu bildirilmiştir. 18 Lakhan ve ark. da postoperatif ağrının tedavisinde aromaterapinin etkili olduğunu bildirmişlerdir.…”
Section: Discussionunclassified
“…da sistematik derlemelerinde, benzer şekilde ada çayı ile yapılan aromaterapinin sezaryen sonrası sedatif etkiye sahip olduğunu bildirmişlerdir. 18 Yine Di Vito ve ark. da obstetride aromaterapinin etkinliğini değerlendirdikleri çalışmalarında, aromaterapinin anksiyeteyi azaltmada etkili olduğunu rapor etmişlerdir.…”
Section: Discussionunclassified
See 2 more Smart Citations
“…Diabetes with induction in the secretion of inflammatory mediators by macrophage cells results in prolongation and an increase in inflammation, thereby delaying wound healing. [114][115][116][117][118][119][120][121] Therefore, the researchers fabricated CUR-loaded CTS NPs (CUR-CS-NPs) to evaluate their capability in a decrement in macrophage cellmediated inflammation and accelerating wound healing in a STZ-induced diabetic rat model. The findings revealed that CUR-CS-NPs with sustained drug release and better cell uptake, through the reduction in inflammation of macrophages and increment in angiogenesis, effectively accelerated the process of wound healing in comparison to the control group.…”
Section: Nanoparticlesmentioning
confidence: 99%